New ICT capabilities in benefiting the Local Authorities (Leicester City Council case) - Bekbota, Bauyrzhan (2014)
This report studies how IT systems could benefit the Revenue and Benefits department at Leicester council. The literature review discusses broad aspects of organisational environment, the stakeholders, value and value flow analysis as on the other side looks to innovation management and processes preparing the organisation for change. With the technology development, introduced by cloud computing, web 2.0 and big data analytics, which is shifting the way businesses run, providing the ability to make decisions based on data which is hold by organisation and external sources like social media. While today big businesses use the technology to get customer insights and provide better experience, which drives profits for organisations. The analysis highlights that although the Council is providing the services at considerable level. The way the IT systems used is far from efficient, represented by the complexity of business model leading to the high number of software products in use, low automatic updates and cross checking, duplication in business processes, slow processing time and absence of decision making support system. At the same time maintaining the ICT infrastructure reflects by costs in terms of manpower, hardware and software. It is recommended that Leicester City Council:  Build a strong team for change and innovations initiatives  Shift to cloud infrastructure  Apply Web 2.0 applications  Apply Big Data Analytics and Business Intelligence tools